Functional status of pediatric patients after extracorporeal membrane oxygenation: A five-year single-center study - Yang Yuhang; Yang Ni; Zhang Tiening; Wang Lijie; Xu Wei; Liu Chunfeng (Frontiers in Pediatrics, 2022)
ObjectiveExtracorporeal membrane oxygenation (ECMO) is a widely used treatment for circulatory and pulmonary support in newborns and young children. Over the past decade, the number of children successfully treated with ECMO has gradually increased. However, despite an increasing number of survivors, new morbidity and long-term health issues are becoming more prevalent. A better understanding of the pediatric ECMO prognosis contributes to improved treatment and care programs and minimizes the risk of sequelae and dysfunctions. We aimed to determine the incidence of new morbidity, prognoses, and follow-up data of survivors treated with ECMO in pediatric intensive care units (PICU) using the Functional Status Scale (FSS).MethodsWe retrospectively collected and analyzed clinical data of patients in the PICU who received ECMO from January 2016 to January 2020. Clinical and functional outcomes were assessed at admission and discharge using the FSS. Twenty-seven patients aged between 1 month and 14 years who received ECMO in the PICU were included. Fifty-two percent were male, and the median age was 36 months (interquartile range, 21–114 months). The patients were admitted for fulminant myocarditis (n = 13), acute respiratory distress syndrome (ARDS) (n = 11), and septic shock (n = 3).ResultsThis study reviewed a single-center experience using the FSS for ECMO treatment in a PICU. The patients' original conditions included fulminant myocarditis, ARDS, and septic shock. Of the 27 patients who received ECMO, 9 (33%) died, 12 (67%) showed improved condition, and 6 (33%) discontinued treatment and left the hospital. Furthermore, the following adverse events were observed in the survivors who were discharged: nine (50%) cases of lower extremity deep vein thrombosis, seven (39%) jugular vein thrombosis, six (33%) acute kidney injury, five (27%) intracranial hemorrhage and cerebral infarction, and one each of (6% each) pulmonary embolism and peripheral nerve injury. Of the 12 patients who survived through 1 year after discharge, five (42%) recovered completely, whereas seven (58%) showed mild to moderate communication and motor dysfunction. The short-term survival rate and 1-year survival rate of ECMO patients were 67% (18/27) and 44% (12/27), respectively. Additionally, approximately one-third of the patients developed a new morbidity after ECMO treatment (6/18).ConclusionsHigh mortality and new morbidity were common in patients who received ECMO treatment. New morbidity increased the risk of death and exacerbated the functional state. Follow-up and rehabilitation after discharge are essential to achieve positive outcomes.